PENINGKATAN HASIL BELAJAR PPKN PADA KURIKULUM MERDEKA MATERI MEMBANGUN JATI DIRI DALAM KEBINEKAAN MENGGUNAKAN MEDIA AUDIO-VISUAL UNTUK SISWA KELAS IV SDN 2 SADANG: penelitian tindakan kelas - Muftia Salsabilla; Erik Aditia Ismaya; Wawan Shokib Rondli (STKIP Subang, 2023)
This study uses the student team achievement (STAD) model and audio-visual media to increase Civics learning in Merdeka Class IV at SDN 2 Sadang. This research uses the student team achievement (STAD) model and audio-visual medium to improve civics learning in unit 3